Accounting: Text and Cases/Accounting Principles (Book). - Hendrickson, Harvey S.; Goetz, Joe F. (The Accounting Review, 1985)
Reviews two books by Robert N. Anthony and James S. Reece. "Accounting: Text and Cases" ; "Accounting Principles."